UJI KEMAMPUAN NaOH UNTUK RECOVERY KROMIUM (III) DARI LIMBAH CAIR PENYAMAKAN KULIT DENGAN METODE PENGENDAPAN - Sri Hastutiningrum; Eko Sugiharto; Mudasir Mudasir (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2007)
Waste from lather tanning process represant one of the pollutants coming from various existing industries. pollutant could affect not only human being, but also affect surrounding other living organism. one of dangerous compounds such as chromium (III) containing inthe liquid waste of leather tanning industry in Yogyakarta has been investigated using precipitation methods. Chromium (III) recovery process is one of simple techniques to recover chrromium (III) from liquid waste of leather tanning. In this technique chromium (III) was converted into its hydroxine and after being seperated, the precipitate was dissolved again in sulfuric acid for further reusing in leather tanning process. in general, the recovery of chromium (III) procedure was started by meausurement oh initial pH, iltration of liquid waste and precipitation of chromium(III) using NaOH. The addition of NaOH eas also intended to increase the pH of the liquid waste. The liquid waste solution was then aged for several hours at varios pH to obtain optimum conditions of precipitation. Obtained precipitatewas filtered using varios paper filters and finally sollution was analized for its chromium(III) content to determine the effectiveness of the recovery. result the study of the study show that whatman 40 paper filter is more appropiate filter for separating chromium. (III) precipitete because this filter gives the highest content of chromium(III) in the recovered solution. The precipitation of chromium (III) proceedseffectivelly in the solution pH of 8 with recovery effeciency of 52,01%, while the effective time of aging was found to be 24 hours with recovery efficincy of 80,39%. From this study, it has been demontrated that liquid waste chromium(III) from leather tanning may be reused as additive materials in the leather tanning process after being recovery from the liqiud waste using precipitation methode.